Secure Approach To Data Transmission Using Steganography and RSA Technique Through TCP/IP Header - Sah, Basant; Jha, V .K (International Journal of Computer Sciences and Engineering, 2018)
This is the time of web, in which whole world is associated with one another, thus significance of security builds step by step. To protect the data from unauthorized user, it is the new challenge for us so that we developed a very simple technique to transfer the data from one party to other by secure channel. As we know that Steganography is a digital technique for hiding information in some form of media, such as image, audio or video. Steganography has advanced routine with regards to hide information in bigger document so that others can't associate the nearness with a shrouded message. In this paper, we outline a framework, which utilizes highlights of both cryptography and in addition steganography, where TCP/IP header is utilized as a steganographic transporter to hide encrypted data. [1] Steganography is a valuable apparatus that permits secretive transmission of data over the correspondences channel. [2] In this paper we have use the MKA algorithm [4] to embed the data inside the image so that capacity of data will be large.